Spirulina platensis Alleviated the Hemotoxicity, Oxidative Damage and Histopathological Alterations of Hydroxychloroquine in Catfish (Clarias gariepinus) - Sayed, Alaa El-Din H.; Hamed, Mohamed; Soliman, Hamdy A. M. (Frontiers in Physiology, 2021)
Pharmaceutical drugs in the aquatic environment can induce adverse effects on non-target organisms. The current study aims at evaluating the toxicity of hydroxychloroquine (HCQ) as pharmaceuticals residue in catfish (Clarias gariepinus) and the protective role of Spirulina platensis (SP). Four groups were used in this study:(1) a control group, (2) a group exposed to 3.16 mg/L of HCQ, (3) a group exposed to 3.16 mg/L of HCQ +10 mg/L of SP, and (4) a group exposed to 3.16 mg/L of HCQ +20 mg/L of SP for 15 days of exposure. The hydroxychloroquine-treated group showed a significant decline in the hematological indices, glucose, total protein, and antioxidants levels in relation to the control group, whereas the hydroxychloroquine-treated group showed a significant increase in the levels of creatinine, uric acid, aspartate aminotransferase (AST) and alanine aminotransferase (ALT) as well as the percentage of poikilocytosis and nuclear abnormalities of RBCs in relation to the control group. The histopathological evaluation of the liver indicated dilation of central vein, vacuolization, degeneration of hepatocytes, and pyknotic nuclei as well as reduction of glomeruli, dilation of bowman's space, and degeneration of renal tubules in the kidney of the hydroxychloroquine-treated group. Spirulina platensis (SP) reduced the elevated levels of liver and kidney functions, poikilocytosis, and nuclear abnormalities of RBCs. Likewise, SP restored the depleted antioxidant defense system, the hematological indices, glucose, and total protein levels as well as rendered the histological architecture to normal status in a dose-dependent manner. Accordingly, the current study recommends the use of Spirulina platensis (SP) to remedy the toxic effects of hydroxychloroquine (HCQ).